Social Capital and Non-Smoking Behavior Among University Students: Implementation of Social Cognitive Theory - Lizya Anggita Abriyanti; Argyo Demartoto; Bhisma Murti; Endang Sutisna Sulaeman; Revi Gama Hatta Novika (Journal of Health Promotion and Behavior, 2025)
Background: Smoking is a habit that has a negative impact on health and the environment, especially among college students. Smokers in Malang Regency are dominated by the age group of 20-24 years old as much as 38.01%. This study aims to analyze the influence of social capital on non-smoking behavior in students by applying Social Cognitive Theory (SCT). Subjects and Method: This cross-sectional study was conducted in Malang, East Java, Indonesia, from December 2024 to January 2025. A sample of 200 male students was selected using random sampling. The dependent variable was non-smoking behavior. Independent variables were social capital, observational learning, self-efficacy, attitude, and outcome expectations. Data were analyzed using STATA 13. Results: Students' non-smoking behavior was directly influenced by social capital (b=0.07; 95% CI= 0.01 to 0.12; p= 0.013), self-efficacy (b=0.52; 95% CI= 0.44 to 0.61; p <0.001), attitude (b=0.41; 95% CI= 0.31 to 0.50; p <0.001), and age (b=-0.07; 95% CI=-0.13 to -0.02; p= 0.008). Meanwhile, the indirect influence was observational learning (b= 0.12; 95% CI= -0.00 to 0.24; p= 0.056), and expected outcome (b=0.31; 95% CI= 0.19 to 0.43; p <0.001). Conclusion: The non-smoking behavior of students is directly influenced by social capital, self-efficacy, attitude, and age. While the indirect influence is observational learning, and the expectation of results.